Control of switch-sharing-based multilevel inverter suitable for photovoltaic applications - Jamaludin, Jafferi; Syamsuddin, Syarkawi; Rahim, Nasrudin Abd; Hew, Wooi Ping (Elsevier, 2018)
Owing to the higher amount and the better quality of power transferred, three-phase multilevel inverters have strengthened their presence in low-power photovoltaic (PV) applications. However, the existing topologies investigated for low-power PV systems are basically meant for medium- and high-power applications, thus making them underutilized for low-power range. In order to address this shortcoming, this paper proposes a three-phase multilevel inverter with a switch-sharing capability and its control solution. It combines the characteristics of the two-level full-bridge topology and the diode-clamped multilevel structure. As a result, the inverter can be used with full capacity and without being underutilized, and significantly improves the output quality. A control strategy that is able to maximize the full potential of the inverter is developed. A digital proportional-integral (PI) controller with a new tuning algorithm is designed to effectively deal with the load changes. The result reveals that the load current is always retained at the intended quality level despite the variations in load. The performance of the inverter is validated from the experimental work conducted on a laboratory prototype under closed-loop conditions.